﻿Morphological characteristics and phylogenetic evidence reveal two new species of Acremonium (Hypocreales, Sordariomycetes) - Xin Li; Zhi-Yuan Zhang; Yu-Lian Ren; Wan-Hao Chen; Jian-Dong Liang; Ji-Mei Pan; Jian-Zhong Huang; Zong-Qi Liang; Yan-Feng Han (MycoKeys, 2022)
Using chicken feathers as bait, Acremonium globosisporum sp. nov. and Acremonium curvum sp. nov. were collected from the soil of Yuncheng East Garden Wildlife Zoo and Zhengzhou Zoo in China. They were identified by combining the morphological characteristics and the two-locus DNA sequence (LSU and ITS) analyses. In the phylogenetic tree, both new species clustered into separate subclades, respectively. They were different from their allied species in their morphology. The description, illustrations, and phylogenetic tree of the two new species were provided.